Conducting a needs analysis - McArdle, Geri (Crisp Pub. Menlo ParkUS, 1998)
Explains the needs analysis process, and its usefulness in understanding, identifying and addressing organizational needs. Provides methodologies and sample materials for the 4-step process: surveillance, investigation, analysis, and report. Includes guidelines for analysing the situation; gathering, organizing and evaluating data; and assessing the need for training.